Manual de Procedimientos Contables y Administrativos, para la Empresa Llantera y Servilujos DENCAR de la Ciudad de Loja. - Aldaz Rodríguez, Joteline Fernanda (2022)
The current research work of the degree, named "MANUAL OF ACCOUNTING AND ADMINISTRATIVE PROCEDURES FOR THE TIRE COMPANY AND SERVILUJOS DENCAR IN LOJA CITY", is directed at analyzing the accounting and administrative areas of the company in order to facilitate the correct performance of the activities that people who work in these areas do daily, increasing its efficiency and effectiveness through objective implementation and trustful-appropriate information obtainment. To fulfill the current degree work objectives, it has taken into account the methods and techniques which help us to verify the information and the use of accounting and administrative procedures manual. To get these results, it is collected information from different sources that helped us to structure the search work before mentioned. Likewise, it is analyzed and made the integral organigram update of the company, where it is implemented the required areas according to the current necessities and the business's turning, provoking new jobs’ positions. It also designed a job’s position organigram about the company's positions and units, informing how many workers are required for each working area depending on the economic activity. In addition, it is done the principal functions of the company's employee with the objective of obtaining an adequate performance for each of the areas; this is carried out by making functions’ registers which contain identification, main proposal, description of the main functions, basic or essential knowledge, and finally the experience that it requires. On the other hand, for the account area, it was designed as a manual appropriate-accounting plan, neat, detailed and encoded according to the activity that the Tire Company and Sevilujos DENCAR performance. This information had the objective of developing the banks entries in different processes as well as designing flow-charts of the principal accounts such as: cashier, small cashier, banks, accounts for receivable, merchandise inventory, property, plant, equipment, depreciation, accounts payable, sales, wages and salaries with respective policies, procedures, examples, and the account entry record; for the administrative area, procedures and policies were developed such as: selection, evaluation, training, staff incentives, as well as control of attendance, punctuality, and prohibitions that the company has with its workers to refine customer service. 5 At the end of the degree work, it is determined that a manual about accounts and administrative procedures for the Tire Company and Servilujos DENCAR constitutes a tool which allows control of the accounts operations and monitoring the administrative activities that happen in the company.